2017
DOI: 10.1158/2159-8290.cd-17-0375
|View full text |Cite
|
Sign up to set email alerts
|

VHL Deficiency Drives Enhancer Activation of Oncogenes in Clear Cell Renal Cell Carcinoma

Abstract: Protein-coding mutations in clear cell renal cell carcinoma (ccRCC) have been extensively characterized, frequently involving inactivation of the von Hippel-Lindau ( VHL ) tumor suppressor. Roles for noncoding cis -regulatory aberrations in ccRCC tumorigenesis, however, remain unclear. Analyzing 10 primary tumor/normal pairs and 9 cell lines across 79 chromatin profi les, we observed pervasive enhancer malfunction in ccRCC, with cognate enhancer-target genes associated with tissue-specifi c aspects of malignan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
127
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(146 citation statements)
references
References 118 publications
11
127
0
Order By: Relevance
“…1). Increased expression of ZNF395 had been previously identified as a potential ccRCC biomarker, and this study demonstrated that knockdown of ZNF395 significantly decreased cell proliferation and viability both in vitro and in vivo in two cell line models of ccRCC, A-498 and 786-O, which highlights the importance of this master regulator and its potential as a therapeutic target (6).…”
supporting
confidence: 54%
“…1). Increased expression of ZNF395 had been previously identified as a potential ccRCC biomarker, and this study demonstrated that knockdown of ZNF395 significantly decreased cell proliferation and viability both in vitro and in vivo in two cell line models of ccRCC, A-498 and 786-O, which highlights the importance of this master regulator and its potential as a therapeutic target (6).…”
supporting
confidence: 54%
“…The copy numbers of 587 ccRCC tissues and 901 paired normal kidney tissues from the TCGA database (KIRC CNV) were obtained. GSE76207 (14) and GSE102101 (15) were obtained from the GEO database (http://www.ncbi.nlm. nih.gov/geo/), and respectively contained 16 and 10 paired tumor and normal kidney tissues.…”
Section: Methodsmentioning
confidence: 99%
“…TF peak calls were downloaded from ChIP-seq analyses performed by 39 . For each T/N/d state, enrichment odds ratios was evaluated by a Fisher’s exact test comparing the number of asQTL peaks overlapping TF peaks (i.e.…”
Section: Methodsmentioning
confidence: 99%